Concentrações e fluxos de nutrientes no gotejo e escorrimento do tronco de Fraxinus angustifolia Vahl. - Madeira, Manuel (2010)
The effect of the ash-tree (Fraxinus angustifolia Vahl) crown on characteristics of throughfall and stemflow solutions was assessed in wet pastures located in north eastern Portugal. The amounts de gross rainfall, throughfall and stemflow were measured continuously and samples were periodically collected to determine pH, dissolved organic C (DOC) and N (DON), and nutrients. The annual fluxes of DOC, DON, Cl, K, Na, Ca, Mg and P in gross rainfall were, respectively, 3.93, 0.92, 0.20, 0.06, 1.81, 2.40, 1.11, 1.16, 0.29 and 0.06 g m-2, while those regarding throughfall were 4.42, 0.20, 1.82, 1.82, 0.31, 0.54, 0.62 and 0.20 g m-2; the flux of N-NH4 + was nil and that of N-NO- 3 was negative (-0.03 g m-2). The fluxes in relation with stemflow were small if expressed on a tree crown projection area basis, but can be much greater if the actual area affected is considered. The amounts and distribution of nutrients turned to the soil by throughfall and stemflow may lead to soil chemical characteristics differentiation beneath tree crowns-------------------Avaliou-se a concentração e os fluxos de nutrientes no gotejo e no escorrimento do tronco de freixo (Fraxinus angustifolia Vahl), num lameiro do Nordeste de Portugal. A precipitação bruta, a precipitação sob coberto (throughfall) e o escorrimento do tronco (stemflow) foram objecto de monitorização e amostras foram colhidas periodicamente para determinação do pH, dos teores de carbono (COD) e azoto (NOD) orgânicos dissolvidos e de nutrientes. Os fluxos anuais de COD, NOD, Cl, K, Na, Ca, Mg e P na precipitação bruta foram, respectivamente, 3.93, 0.92, 0.20, 0.06, 1.81, 2.40, 1.11, 1.16, 0.29 e 0.06 g m-2, enquanto no gotejo foram de 4,42, 0,20, 1,82, 1,82, 0,31, 0,54, 0,62, 0.20 g m-2; o fluxo de N-NH4 + foi nulo e o de N-NO- 3 foi negativo (-0,03 g m-2). A expressão dos fluxos devido ao escorrimento do tronco variará com a área influenciada por esta solução. A restituição de nutrientes ao solo pelo gotejo e pelo escorrimento do tronco poderá contribuir para diferenciar as características do solo sob a copa das árvores.